If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(5f + 5) = 0 Reorder the terms: 2(5 + 5f) = 0 (5 * 2 + 5f * 2) = 0 (10 + 10f) = 0 Solving 10 + 10f = 0 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 10f = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 10f = 0 + -10 10f = 0 + -10 Combine like terms: 0 + -10 = -10 10f = -10 Divide each side by '10'. f = -1 Simplifying f = -1
| x-(x*.0765)=200 | | f(t)=-4t^2+16t+9 | | -3j-(-4)/-6-12 | | 3x+21=13x+59 | | -8+2m=-16.4 | | -4x=-250 | | x^2-16x+35=0 | | 2(6X)-4=32 | | 178-x=254 | | 17 = g3+ 13 | | 8x+36+5x+60= | | 2/7x=100 | | 2(-5-x)+6x-7=5 | | a+5=42*6 | | 9/11=-19/x | | 72x-78=30 | | 14=3+b+5 | | 5x=80+15 | | -1+8(x-2)=15x+3-7x | | 7x/x-60 | | 7x/x-69 | | -3-3(0)=0 | | 6(-2n+4)-2n=-6+3 | | 35+5a=10 | | (8-2x)/6=15 | | Y+(7y+21)=2Y+45 | | -3x^2-150=0 | | 6t-5=2t+9 | | 6(x-2)-8x=-26 | | y+4=2x+6 | | 0.50x+0.15(50)=34.5 | | 2(0)+3y=36 |